Exploration of the Need for Developing ARCS Model-Based E-Module in Biology Learning: A Mixed-Methods Study - Naadhiroh, Naila Zulfa; Sunardi, Sunardi; Sukmawati, Fatma (Universitas Muhammadiyah Mataram, 2026)
This study addresses the limited use of interactive digital teaching materials and the low level of student motivation in Biology learning. This study aims to analyze needs and explore the potential for developing e-modules based on the ARCS (Attention, Relevance, Confidence, Satisfaction) model in Biology learning. The research employs a mixed-methods approach with an exploratory sequential design. The qualitative phase involved interviews with three teachers, while the quantitative phase included 198 students through a distributed questionnaire. The results indicate that Biology learning still faces various challenges. Teachers reported that common teaching obstacles relate to student motivation and stated unfamiliarity with, and lack of implementation of, the ARCS model in their teaching. The majority of students expressed a desire for teaching materials that are more engaging and enjoyable, supplemented with images, animations, or videos. Both students and teachers showed interest in developing e-modules, viewing these as resources that can enhance motivation, facilitate understanding of the material, and support independent learning. These findings suggest that the ARCS-based e-module holds potential as a relevant solution for improving the quality of Biology learning through a motivational approach. This study provides a foundation for the development of the ARCS model-based e-module and recommends opportunities for further research on its effectiveness.